Protocol for Xenium spatial transcriptomics studies using fixed frozen mouse brain sections - Xiaokuang Ma; Peng Chen; Jing Wei; John Zhang; Chang Chen; Hanqiu Zhao; Deveroux Ferguson; Aaron W. McGee; Zhiyu Dai; Shenfeng Qiu (STAR Protocols, 2024)
Summary: Here, we present a protocol for Xenium spatial transcriptomics studies using fixed frozen mouse brain sections. We describe steps for intracardiac perfusion, cryosectioning, and floating section mounting of brain sections, which enable runs on the Xenium analyzer and data delivery. We demonstrate that, in addition to the 10× Genomics-validated formalin-fixed paraffin-embedded (FFPE) and fresh frozen sections, fixed frozen thin brain sections are compatible with the Xenium platform and provide excellent imaging and quantification results for spatially resolved gene expression.For complete details on the use and execution of this protocol, please refer to Ma et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.